O não-teísmo budista: o imaginário do divino dos budistas brasileiros do Templo Odsal Ling - Ramos, Danielle Mozena (2013)
This research's objective is to study how Brazilians from the Tibetan Buddhist Tradition (from the Odsal Ling Temple, Nyingma School) conceive the idea of the Absolut, in other words, understood as the "divine" at the Buddhist universe (which is non-teist) − concentrating mainly in philosophical definitions from the Tibetan Buddhism. To do that, it will be presented some conceipts, which are: compassion, bodhichitta and emptiness. These three elements are didatic steps that Tibetan Buddhism uses to work and wake Buddha's Nature, recognizing the same perfect nature in all beings and all things. After this first part, the research will focus in the analysis of how this non-teistic point of view is conceived and seen by the Brazilians from the Tibetan Buddhism (concerning Odsal Ling Temple), identifying languages and sincretisms with Brazilian religiosity and questioning the difficulty of the Brazilian adept in adopting this religious way